ANALYSIS OF FINANCIAL PERFORMANCE COMPANY MULTIFINANCE POST YEAR 2004-2008 ECONOMIC CRISIS (CASE STUDY ON MULTIFINANCE COMPANY IN INDONESIA) - One, Mansur; Isafaatun, SE., MM, Eliya (Accounting, 2009)
Multifinance company or finance company, viewed from the multi-finance company activities provide a variety of services ranging from consumer credit, leasing (leasing), factoring (factoring), business loans, credit cards and many more services provided to meet local needs funds and goods. In the first year 2004, total financing of multi-finance companies to reach Rp 44 trillion or an increase of 40.27% from the year 2003 amounting to Rp 31 trillion, in 2005, the performance of finance companies experienced impressive growth, from 141 multi-finance companies in Indonesia, the total financing of Rp 61 trillion or an increase of 36.68% from 2004. (Rully Ferdian, "Rating 130 Multifinance", InfoBank, Edition August, 2006, p.11). In the year 2004-2007 shows that the financing company is good in terms of level of liquidity, while its solvency level is good, and viewed from the level of activity of the total assets of finance companies is not good and the net profit margin of profitability could also be said whether this indicated the existence of company are able to increase profitability and 100% of the PT. Buana Finance in 2007. Keywords: multifinance.